ÁP DỤNG PHƯƠNG PHÁP ĐIỆN TỪ TẦN SỐ THẤP DÙNG THIẾT BỊ ERA TRONG NGHIÊN CỨU DI TÍCH HOÀNG THÀNH THĂNG LONG - Ninh, Dương Thị; Lụa, Mail Thị; Thùy, Đặng Ngọc; Vũ, Trần Anh; Phòng, Lại Hợp (Vietnam Journal of Earth Sciences, 2012)
Application of low frequency electromagnetic investigation by using equipment ERA in the archaeological site of Thang Long Citadel The Thang Long Citadel is the Imperial Palace of the Vietnam since 11th Century. Thus, the architectures developed in this place are characterized the cultural quintessence of Vietnamese along history. Most of the structures constructed by different dynasties were destroyed and scattered in terms of the archaeological buried remains. Non-destructive identification of these objects is significance for the restoration and preservation of cultural heritage. For this purpose, the exploration was carried out by using geophysical methods during the last years, such as: resistivity, seismic, magnetic, ground penetrating radar, γ-γ and η-η loging measurements. Since the noise produced by the urban activity and city liveline systems is strongly affected to the quality of the geophysical observational data, the problem can be successfully solved by applying combination of several methods. Among them the low frequency electromagnetic investigations conducted by the new equipment ERA having more advantage to apply in the field measurements, which reduced the noise produced by the city electric systems and can be realized in the complicated environment. This paper present some results derived from the measurements by using ERA equipment in the Thang Long Citadel site.